The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1302/0301-620x.95b2.29491
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for overgrowth after flexible intramedullary nailing for fractures of the femoral shaft in children

Abstract: We analysed retrospectively the risk factors leading to femoral overgrowth after flexible intramedullary nailing in 43 children (mean age 7.1 years (3.6 to 12.0)) with fractures of the shaft of the femur. We reviewed their demographic data, mechanism of injury, associated injuries, the type and location of the fractures, the nail-canal diameter (NCD) ratios and femoral overgrowth at a mean follow-up of 40.7 months (25.2 to 92.7). At that time, the children were divided into two groups, those with femoral overg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…In line with our findings, Fakoor et al [19] also reported that age, gender, weight and fracture location had no effect on postoperative length changes. Moreover, the results of our study also suggested that concomitant head trauma and the cause of injuries had no significant relationship with limb overgrowth, which was consistent with Park's results [20].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, Fakoor et al [19] also reported that age, gender, weight and fracture location had no effect on postoperative length changes. Moreover, the results of our study also suggested that concomitant head trauma and the cause of injuries had no significant relationship with limb overgrowth, which was consistent with Park's results [20].…”
Section: Discussionsupporting
confidence: 92%
“…81 Age, size of child and the site and pattern of the fracture are factors that govern the type of operative management, including the use of an ESIN, internal fixation with a plate via a traditional open or a minimally invasive approach, external fixation, and even rigid intramedullary fixation. [82][83][84][85][86][87] The forms of surgical treatment available for the management of these fractures in children over five years of age have evolved significantly over time, partly influenced by socioeconomic factors, as a shorter hospital stay was thought to have psychological, educational, social and economic advantages. 88 Before this, these children were usually managed with a hip spica.…”
Section: Fractures Of the Femoral Shaftmentioning
confidence: 99%
“…Complications due to flexible intramedullary nails to treat pediatric diaphyseal femur fractures include loss of reduction, nonunions, malunion and leg length discrepancy ( 2 ). Symptomatic hardware can be seen in up to 23% of patients ( 3 ).…”
Section: Discussionmentioning
confidence: 99%